Analisis Status Gizi Pada Lanjut Usia - Rizqi Ramadhan (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
The general objective of this research is to find out the description of the nutritional status of the elderly at the Wredha Wana Sraya Denpasar Home and specifically to find out the Body Mass Index (Weight, Height), Abdominal Circumference, Upper Arm Circumference (LILA) in the elderly at the Nursing Home. Wana Sraya Denpasar.